Pengaruh Kualitas Layanan dan Kepercayaan Konsumen terhadap Keputusan Pembelian pada Platform ShopeeFood pada Mahasiswa Pendidikan Ekonomi FKIP Universitas Lampung - Catur Febriyan; Sela Ayu Irawati; Muhammad Rizqi Alfiah; Syifa Hesti Pratiwi; Annisa Luthfiyyah; Rahmawati Rahmawati; Fiarika Dwi Utari (Universitas Negeri Padang, 2026)
The way people buy things has changed a lot because of technology. This is especially true when it comes to ordering food from places like ShopeeFood. Since there are many companies that deliver food online it is really important to know what makes people decide to buy from one company or another. This study is looking at how the quality of the service and how much people trust the company affects what students from the Economics Education Program, at Universitas Lampung decide to buy. We did this study by asking people questions and using numbers to understand the answers. We gave questionnaires to 81 students out of 102. Picked them randomly. Then we used a kind of math to analyze the answers. What we found out is that when the service is good and people trust the company, they are more likely to buy food from them. This is true when we look at each of these things separately and when we look at them together. The numbers show that the quality of the service and how much people trust the company can explain why 79.1% of people make the purchasing decisions they do. The other 20.9% is because of things we did not study. So, to sum it up the quality of the service and how much people trust the company are really important when it comes to deciding what to buy on ShopeeFood. Therefore, companies should try to make their service and make people trust them more if they want to get more customers and stay competitive in the food delivery business.